2005
DOI: 10.1042/bj20040694
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminoimidazole-4-carboxamide riboside (AICAR) enhances GLUT2-dependent jejunal glucose transport: a possible role for AMPK

Abstract: AMPK (AMP-activated protein kinase) is a key sensor of energy status within the cell. Activated by an increase in the AMP/ATP ratio, AMPK acts to limit cellular energy depletion by down-regulating selective ATP-dependent processes. The purpose of the present study was to determine the role of AMPK in regulating intestinal glucose transport. [3H]3-O-methyl glucose fluxes were measured in murine jejunum in the presence and absence of the AMPK activators AICAR (5-aminoimidazole-4-carboxamide riboside) and metform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 46 publications
5
114
3
1
Order By: Relevance
“…Of great interest, apical GLUT2 is the target of a cellular energy-sensing mechanism. Energy depletion provokes activation of AMP-activated protein kinase (AMPK), which causes activation of p38 and then insertion of apical GLUT2 (37). The antidiabetic drug metformin also activates AMPK (38) and promotes apical GLUT2 insertion; while this might potentially lead to an increased rate of delivery, glycemic control is in fact better because intestinal utilization is enhanced (39).…”
Section: Regulation Of Apical Glut2mentioning
confidence: 99%
“…Of great interest, apical GLUT2 is the target of a cellular energy-sensing mechanism. Energy depletion provokes activation of AMP-activated protein kinase (AMPK), which causes activation of p38 and then insertion of apical GLUT2 (37). The antidiabetic drug metformin also activates AMPK (38) and promotes apical GLUT2 insertion; while this might potentially lead to an increased rate of delivery, glycemic control is in fact better because intestinal utilization is enhanced (39).…”
Section: Regulation Of Apical Glut2mentioning
confidence: 99%
“…A high sugar intake is a physiological regulator of this process, increasing monosaccharide uptake threefold in vivo (6). The recruitment of GLUT2 in BBM was also observed in conditions of increased calorie demand and glucagon-like peptide 2 treatment (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…It has also been reported that both IPC and heat shock induced protection occurs via the AMPK activation in liver and heart [16,23,24]. Heart treated with AICAR, an activator of AMPK, affords protection against injury during sustained I/R [25,26]. In summary, these reports suggest that AMPK plays an important role in the process of cardioprotection.…”
Section: Introductionmentioning
confidence: 70%
“…Recently, it has been reported that AMPK prevents ischemic injury in the hearts [21,22], and that IPC and heat shock induced protection occurs via AMPK activation in liver and heart [16,23,24]. Furthermore, AICAR affords the protection against I/R injury [25,26]. Therefore, AMPK has emerged as a new pathway that plays an important protective role in the process of cardioprotection.…”
Section: mentioning
confidence: 99%